Integration of Neurofeedback and Virtual Reality - Innovative approaches to the clinical practice of Attention Deficit Hyperactivity Disorder - Rocha, Paula; Ribeiro, Diamantino (Seven Editora, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder characterized by symptoms of inattention, hyperactivity, and impulsivity, which can have an important impact on people's daily functioning and quality of life. Traditional treatment methods, including medication and behavioral therapy, often have limited success and present several challenges. Recent technological developments provide promising alternatives, notably through the integration of neurofeedback and virtual reality (VR) into clinical practice. This article explores the potential of combining these innovative tools to improve the treatment of ADHD. Neurofeedback, a technique that trains individuals to regulate brain activity, has been shown to be effective in managing ADHD symptoms. Similarly, VR provides immersive and engaging environments that can be adapted to therapeutic needs. By combining neurofeedback with VR, practitioners can create interactive and personalized treatment protocols aimed at improving patient engagement, adherence, and outcomes. In this paper, we discuss the mechanisms of action, current applications and empirical evidence supporting the use of neurofeedback technologies  and VR in the treatment of ADHD.  DOI:https://doi.org/10.56238/sevened2024.016-001